AB0615 MORTALITY AND CAUSES OF DEATH AMONG ROMANIAN SYSTEMIC SCLEROSIS PATIENTS. (2nd June 2020) - Petcu, A.; Tamas, M. M.; Muntean, L.; Simon, S. P.; Filipescu, I.; Damian, L.; Leucuta, D. C.; Rednic, S.
Abstract : Background: Systemic sclerosis (SSc) is associated with an increased risk of death compared to the general population. Survival in SSc patients has improved significantly over the last 20 years with a decrease in renal involvement as a cause of early death and an increase in death caused by cardiopulmonary involvement (1, 2). Causes of death in SSc patients have not been described in a Romanian cohort so far. Objectives: To study the causes of death in patients with SSc prospectively followed-up from 2002 to 2018 in a single tertiary centre from Romania. Methods: The cohort consists of 197 patients who fulfill the American College of Rheumatology /EULAR 2013 criteria for SSc. We examined the data of patients who had died during follow up. Patients were reviewed at least twice a year and the cause of death was classified as SSc-related or nonSSc-related. SSc-related deaths were then attributed to the major organ involved. A univariate Cox proportional hazard (PH) regression was used to examine the association between each variable and mortality. Variables reported in the literature to associate with mortality were considered in the multiple Cox PH regression model. Results: Of 197 SSc patients (87.8% females), 47.7% had diffuse SSc and 52.2% had limited SSc. The mean age at diagnosis was 47 (SD 12) years and mean follow up duration was 6.75 years. There were 41 deaths (20.8%). Survival rate was substantially lower in men (P <0.003). The mean age at the time of death in those with diffuse SSc was lower compared to limited SSc (55.8 years vs 68.7 years). Sixty percent of deaths were SSc-related (pulmonary cause[n=11], cardiac cause[n=6], gastrointestinal involvement [GI, n=3], renal crisis [n=2] and others [n=4]). Deaths no related to SSc were associated with cancer and infections. Age at onset of Raynaud phenomenon [HR 1.05], male gender [HR 3.41], diffuse SSc [HR 0.48], presence of tendon friction rub [HR 4.54], digital ulceration [HR 3], esophagitis [HR 2.07] and cardiovascular involvement [HR 3.68], use of corticosteroids[HR 2.13] and cyclophosphamide [HR 2.02] were associated with poor prognosis in multivariate analysis. Conclusion: In our cohort the main causes of death were lung and cardiovascular involvement. Deaths occurred early after the onset of the disease and the survival rate was significantly reduced among men. Multivariate analysis showed that age at onset of Raynaud phenomenon, male gender, diffuse disease form, presence of tendon friction rub, digital ulceration, esophagitis and cardiovascular history, use of corticosteroids and cyclophosphamide were independently associated with mortality. References: [1]Tyndall AJ, Bannert B, Vonk M, Airo P, Cozzi F, Carreira PE, et al. Causes and risk factors for death in systemic sclerosis: a study from the EULAR Scleroderma Trials and Research (EUSTAR) database. Ann Rheum Dis. 2010 Oct;69(10):1809–15. [2]Rubio-Rivas M, Royo C, Simeon CP, Corbella X, Fonollosa V. Mortality and survival in systemic sclerosis: systematic review and meta-analysis. Semin Arthritis Rheum. 2014 Oct;44(2):208–19. Disclosure of Interests: None declared